Anticipatory postural control during arm movements and floor translation - Fujiwara, K. (The Journal of Physical Fitness and Sports Medicine, 2013)
Many researchers have analyzed dynamic postural control during voluntary arm movements and floor translation, focusing on the anticipatory activation of postural muscles in which the function of frontal lobe is involved. In this review, I address the postural muscle activation preceding arm movements, and consider the effect of arm movement dynamics, behavioral condition, postural set and postural movement pattern. I also address the anticipatory postural control during transient or periodical floor translations, and consider motor preparation, attentional allocation, and the use of event-related brain potentials to investigate frontal lobe activation.